d-Alanine Oxidase from Escherichia coli: Localization and Induction by l-Alanine - Raunio, R. P. (1973)
Dialyzed membranes of Escherichia coli prepared by an ethylenediaminetetraacetic acid-lysozyme method catalyze the oxidation of both l-alanine and d-alanine. The specific activities for the oxidations of both d-alanine and l-alanine are increased fivefold when the cells are grown in the presence of either l-alanine or dl-alanine, but are increased only slightly when grown in the presence of d-alanine. In the dl-alanine-induced system, the specific activities for the oxidations of some other d-amino acids are also raised. dl-alanine also induces two other alanine catabolizing enzymes, alanine dehydrogenase and alanine-glutamate aminotransferase which are found in the “soluble” fraction of lysozyme-treated cells. The oxidations of both l-alanine and d-alanine were associated with the membranes of induced cells. After the membranes were disintegrated by sonic treatment, both l-alanine and d-alanine oxidation catalysts sedimented in a sucrose density gradient together with d-lactate and l-lactate dehydrogenases, apparently as a single multienzyme complex.